Tiếp cận tín dụng chính thức trong phát triển chuỗi giá trị nông sản: Động lực cho quá trình tái cơ cấu nông nghiệp tại khu vực Tây Bắc, Việt Nam - Đỗ Xuân Luận; Đỗ Thu Dung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
The study used primary data collected from face-to-face interviews with 163 farm households and relevant stakeholders to analyze credit access constraints of Bat Do bamboo shoots households in Luc Yen district, Yen Bai province, Vietnam. Using a mixed method which integrates quantitative and qualitative analysis, the results show that the credit amount is positively correlated with an increase in income from bamboo shoot cultivation. However, access constraints to formal credit remain and hinder value chain development. Furthermore, households which are members of the Women's Union and have collateral are more likely to access to formal credit while expanding the amount of loans can increase the income of smallholder farm households in the value chain and an increase in capacity building of local unions can help to address asymmetric information issues in rural credit transactions. It is necessary for the government to speed up the granting of land use right certificates to be used as collateral and establish a collaboration platform between banks, farm households, enterprises, cooperatives, and other stakeholders in order to link credit demand and supply for value chain development. In addition, contract farming between farmers and enterprises is needed to reduce market risk and facilitate the approach of value chain-based lending.
Keywords: Constraints; Credit; Northwestern; Bat Do bamboo shoot; Value chain